2021
DOI: 10.1093/cid/ciab142
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Need for Pooled Data on Coronavirus Disease 2019 in African Children: An AFREhealth Call for Action Through Multicountry Research Collaboration

Abstract: Globally, there are prevailing knowledge gaps in the epidemiology, clinical manifestations, and outcomes of SARS-CoV-2 infection among children and adolescents; however, these gaps are especially wide in African countries. The availability of robust age-disaggregated data is a critical first step in improving knowledge on disease burden and manifestations of COVID-19 among children. Furthermore, it is essential to improve understanding of SARS-CoV-2 interactions with comorbidities and co-infections such as HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…COVID-19 has also posed significant obstacles to collecting information on maternal and child nutritional outcomes [53], or standardized indices such as the MDD-W. We retrieved no data on such outcomes. Diet diversity and food security data were collected via phone and online surveys.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…COVID-19 has also posed significant obstacles to collecting information on maternal and child nutritional outcomes [53], or standardized indices such as the MDD-W. We retrieved no data on such outcomes. Diet diversity and food security data were collected via phone and online surveys.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…As is now apparent, many aspects of research and teaching can be continued quite effectively via virtual platforms like Zoom and others. A successful example of the leverage of virtual video platforms for research collaborations is demonstrated by AFREhealth's multi-country, South-South COVID-19 research project among pregnant women and children [7,8]. While deficiencies and concerns in education (especially clinical teaching and training) remain, several have been quite effectively addressed in some form through video-enhanced platforms like Lecturio, Osmosis, and Scholar-X [6].…”
Section: Rethinking Global Health Partnerships: Research and Educationmentioning
confidence: 99%
“…Such initiatives will also strengthen Southto-South multi-disciplinary and interprofessional research collaborations. AFREhealth's COVID-19 Research Working Group has embarked upon such a collaboration across Western, Central, Eastern, and Southern Africa [7,8].…”
Section: South-south and North-south Research Collaboration And Capacity Buildingmentioning
confidence: 99%
“…Although the literature on COVID-19 is growing at an exponential pace, there is still a shortage of observational studies from several African countries. However, local epidemiology is essential to enable the adaptation of the evidence-based response of COVID-19 at local levels as well as national and regional levels, once pooled [ 6 , 7 ]. For example, in typical resource constrained settings, not every facility would have adequate intensive care beds, access to ventilators, continuous oxygen, CT scanners, or even basic biological testing kits.…”
Section: Introductionmentioning
confidence: 99%